THE IMPORTANCE OF E-COMMERCE ON THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN THE RURAL AREA DURING COVID-19 - Yoanita Kartika Sari Tahalele; Marini Yunita Tanzil; Fabio Ricardo Toreh (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The Covid-19 pandemic that has been spreaded on March 2020 in Indonesia has greatly affected the economy and changed the nature of business in Indonesia. The new normal has led to a surge in e-commerce and digital transformation. However those who live in rural areas could not take advantage of this transformation, as they have very minimal access and knowledge about digital literacy. The researchers believe one way to make them know and understand about this matter is through training. Thus, this study aims to understand the importance of e-commerce training on the development of micro, small and medium enterprises (MSMEs) in the field of creative industry in the rural area during Covid-19 Pandemic, using a case study in Biak Numfor, Papua. The analysis is based on a qualitative study using focus group discussion toward 6 women, who have MSMEs in the creative industry in Biak Numfor and have joined e-commerce training. The study assessed that the training is important and provides an understanding about the importance of e-commerce and its significant to help their business development. The results are expected to be able to contribute frameworks and ideas to the community, government, and MSMEs players associated to the importance of e-commerce and the training on the development of MSMEs in the rural area during Covid-19. Keywords: e-commerce, MSMEs, Covid-19, rural area